Activity of layered swedenborgite structured Y0.8Er0.2BaCo3.2Ga0.8O7+δ for oxygen electrode reactions in at intermediate temperature reversible ceramic cells. Issue 1 (17th December 2020) - Shin, Ji-Seop; Park, Hyunyoung; Park, Kwangho; Saqib, Muhammad; Jo, Minkyeong; Kim, Jung Hyun; Lim, Hyung-Tae; Kim, Minseuk; Kim, Jongsoon; Park, Jun-Young
Abstract : A new class of layered swedenborgite structured Y0.8 Er0.2 BaCo3.2 Ga0.8 O7+δ is proposed for oxygen electrode reactions in reversible ceramic cells because of its low thermal expansion and high chemical bulk diffusion coefficients. Abstract : To improve the thermal stability and intrinsically sluggish kinetics of oxygen electrode reactions in solid oxide fuel cells (SOFCs) and reversible protonic ceramic cells (RPCCs) at intermediate temperatures, a novel layered swedenborgite structure Y0.8 Er0.2 BaCo3.2 Ga0.8 O7+ δ (YEBCG) catalyst is introduced as an alternative to perovskite materials that contain cobalt. The thermal expansion coefficient of YEBCG is 8.41 × 10 −6 K −1, which is relatively well matched to the state-of-the-art proton-conducting and oxygen-ion-conducting electrolytes. The chemical bulk diffusion and surface exchange coefficients of YEBCG are 7.12 × 10 −4 and 8.01 × 10 −3 cm 2 s −1, respectively, at 650 °C, which leads to much faster action than with state-of-art perovskite structured materials at intermediate temperatures. The maximum power densities of YEBCG cells are notably high, reaching 0.77 and 0.83 W cm −2 at 650 °C in SOFC and protonic ceramic fuel cell modes, respectively. Under electrolysis, the YEBCG cells achieve outstanding current densities of −0.61 and −4.42 A cm −2 at 500 and 700 °C, respectively, under an applied voltage of 1.4 V. Furthermore, the RPCC with YEBCG present no degradation over an entire 1000 h in fuel cell and electrolysis cell modes. These results demonstrate the excellent properties, including good durability, of the YEBCG air electrode when used in high performance SOFCs and RPCCs.